KLUTUK BANANA (MUSA BALBISIANA COLLA) PEEL FRACTIONS: ANTIOXIDANT AND ANTIHYPERGLYCEMIC POTENTIAL - NOFIANTI, TITA; MUHTADI, AHMAD; FIDRIANNY, IRDA; FUADAH, AI SAMROTUL; NURVIANA, VERA; RUSWANTO (International Journal of Applied Pharmaceutics, 2021)
Objective: The purposes of this research were the antihyperglycemic and antioxidant determination of klutuk banana peel fractions through the oral glucose tolerance test (OGTT) and DPPH (2,2-diphenyl-1-picrylhydrazyl) methods, respectively. Methods: Klutuk banana peel was extracted by reflux method and followed by fractionation using n-hexane and ethyl acetate solvents by liquid-liquid extraction method. The statistical analysis used by one-way ANOVA and post hoc Tukey. Results: The results of OGTT showed that ethyl acetate fraction of klutuk banana peel 14.5 mg/kg bw demonstrated higher activity to decrease blood glucose level compared to the other groups as much-32%,-49%,-47% and-40% at min 30, 60, 90 and 120, respectively. The IC50 of ethyl acetate fraction of klutuk banana peel was 0.3708 µg/ml, and its antioxidant activity index (AAI) 40.45. Conclusion: The ethyl acetate fraction of klutuk peel presented very strong antioxidant and antihyperglycemic activity.